Rancang Bangun Kendali Aircraft Jacking pada Pesawat Boeing 737-800 untuk Pengaturan Sudut Kemiringan - Aditya Ghiffari Rukmananda; Aries Boedi Setiawan; Wahyu Dirgantara (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to design an Aircraft Jacking control system for the Boeing 737-800 to automatically balance the aircraft's inclination using an MPU6050 sensor and servo actuators. The system can detect pitch and roll angles with an accuracy of ±0.5° and an average response time of 150 ms. Based on tests using five datasets, the balancing time ranges from 400 to 600 ms, depending on the initial imbalance. In Dataset 5, with a pitch of 3.5° and a roll of -2.3°, the system required 600 ms to achieve balance, demonstrating its ability to handle critical conditions. The servo actuators successfully adjusted the jacking height within a range of 2 cm with a precision of ±0.02 cm, while the OLED-based monitoring system allowed operators to observe the inclination angles in real-time. Furthermore, ESP-NOW-based communication achieved a data transmission success rate of 98%, supporting efficient centralized control. This research demonstrates the system's effectiveness in balancing the aircraft quickly and accurately, providing a foundation for further development under extreme conditions and energy efficiency improvements.